KEPENTINGAN NICOLAS MADURO MEMUTUSKAN HUBUNGAN DIPLOMATIK DENGAN KOLOMBIA TAHUN 2019 - Zul Alfan; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Venezuela is a rich country bestowed of its oil natural resources. Unfortunately, it has suffered social and economic crises since 2016. Surprisingly, Nicholas Maduro is reelected in February 2019 and simultaneously announced breaking diplomatic relationship with his neighbor country Columbia. Maduro’s big decision to have that policy to Columbia who has political and economic support from the United States intrigued researcher to explain the reasons for Maduro.             Explanation for Maduro’s decision to break diplomatic relationship with Columbia was analyzed with level analysis of individual and international system. Behavioristic theory explained Maduro idiosyncrasy and international support by Russia and China for international system. Data came from books, journals, news, websites, and twitters.            The research showed that political culture of Venezuela enables a president to have a big power in decision making processes. Nicholas Maduro is a strong figure successor of Hugo Chaves who ever challenged the United States of America hegemony in Latin America. America support for logistic at the border between Columbia and Venezuela was assumed as a hostility toward Venezuela. Calculation of support from Russia and China to Venezuela as well as hostility assumption to Venezuela led to Maduro decision to end diplomatic relationship with Columbia who is American satellite.  Keywords: Motivation, Idiosyncrasy, Diplomatic Relationship, Venezuela